Предмет:
Другие предметыАвтор:
аноним- f (x) = - cos (x) / (sin (x) + tg (x) ).
f (- x) = cos (- x) / (sin (- x) + tg (- x) ) = cos (x) / (- sin (x) + (- tg (x) ) ) =
= cos (x) / (- (sin (x) + tg (x) ) ) = - cos (x) / (sin (x) + tg (x) ) = - f (x).
f ( - x ) = - f ( x ), следовательно данная функция является нечётной.
= (cos2 (a) / (sin (a) * cos (a) ) ) * (1 / tg (a) ) =
= (cos (a) / sin (a) ) * ctg (a) = ctg (a) * ctg (a) = ctg2 (a).
Автор:
bryannayo82Добавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть